Efficient and Stable FASnI3 Perovskite Solar Cells with Effective Interface Modulation by Low‐Dimensional Perovskite Layer. Issue 22 (11th October 2019) - Liao, Min; Yu, Bin‐Bin; Jin, Zhixin; Chen, Wei; Zhu, Yudong; Zhang, Xusheng; Yao, Weitang; Duan, Tao; Djerdj, Igor; He, Zhubing
Abstract: The promising tin perovskite solar cells (PSCs) suffer from the oxidation of Sn 2+ to Sn 4+, leading to a disappointing conversion efficiency along with poor stability. In this work, phenylethylammonium bromide (PEABr) was employed to form an ultrathin, low‐dimensional perovskite layer on the surface of the FASnI3 (FA=formamidinium) absorber film to improve the interface of perovskite/PCBM ([6, 6]‐phenyl‐C61 ‐butyricacid methyl) in the inverted planar device structure of the ITO (indium‐doped tin oxide)/PEDOT:PSS [poly(3, 4‐ethylenedioxythiophene)/polystyrene sulfonate]/perovskite/[6, 6]‐phenyl‐C61 ‐butyricacid methyl (PCBM)/BCP (2, 9‐dimethyl‐4, 7‐diphenyl‐1, 10‐phenanthroline) electrode. The device efficiency was enhanced from 4.77 to 7.86 % by this PEABr treatment. A series of characterizations proved that this modification could improve the crystallinity of the FASnI3 perovskite by incorporating Br and forming an ultrathin, low‐dimensional perovskite layer at the interface, which led to the effective suppression of Sn 2+ oxidation, improved band level alignment, and decreased defect density. These effects contributed to the clear enhancement of conversion efficiency. Moreover, this treatment also led to remarkably enhanced device stability, with approximately 80 % of the initial efficiency retained after 350 h light soaking, whereas the control device failed within 140 h. This work deepens our understanding of the suppression effect of PEABr on the oxidation of Sn 2+ and paves a new way to fabricate promising tin halide PSCs by facile interface engineering. Abstract : Treat yo self : Phenylethylammonium bromide (PEABr) is employed to treat pristine FASnI3 (FA=formamidinium) films, leading to formation of an ultrathin low‐dimensional perovskite layer on the surface of the pristine film and Br incorporation into the bulk of the FASnI3 film. The treatment enhances stability and conversion efficiency from 4.77 to 7.86 %.